The dictatorship in the Classical Roman Republic as a prime referent in the regime of the constitutional state of emergency - Siles Vallejos, Abraham (2014)
The starting point of the article is the idea that the original model of state of emergency government established to save the Constitution can be found in the Classical Roman Republic. It makes the characteristics of this institution to be analyzed. Institution that has founded an intellectual ‘tradition’ in the political and legal Western thought. The study also comments the characteristics that distinguish the “Roman dictatorship” as a concept that lightens the theoretical options of people who worry about the constitutional emergencies and the powers to set against.